2013
DOI: 10.1186/1471-230x-13-33
|View full text |Cite
|
Sign up to set email alerts
|

Low rate of recurrence of Helicobacter Pylori infection in spite of high clarithromycin resistance in Pakistan

Abstract: BackgroundThe aim was to investigate the reinfection rate of H. pylori during a follow-up period of 12 months in adults who had undergone eradication therapy.MethodsOne hundred-twenty patients; 116 with gastritis, 3 with duodenal ulcer and 1 gastric ulcer, were studied. Their mean age was 41 ± 13 years (range 18–77) and male: female ratio of 2:1. H. pylori were cultured and antibiotic sensitivity was determined by Epsilometer test (E-test) for clarithromycin (CLR) and amoxicillin (AMX). Primers of urease C gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
3
7
1
Order By: Relevance
“…Female patients had the higher rate of infection with H. pylori microorganism, similar finding was found among Iraqi population in other studies [31,32], inversely, male gender was predominant to females in others [33,34]. Higher percentage of peptic ulcer patients diagnosed endoscopically as duodenal ulcer compared to these with gastric ulcer in the present study.…”
Section: Abbas Et Alsupporting
confidence: 89%
“…Female patients had the higher rate of infection with H. pylori microorganism, similar finding was found among Iraqi population in other studies [31,32], inversely, male gender was predominant to females in others [33,34]. Higher percentage of peptic ulcer patients diagnosed endoscopically as duodenal ulcer compared to these with gastric ulcer in the present study.…”
Section: Abbas Et Alsupporting
confidence: 89%
“…post-eradication therapy, these results were in agreement with Sekine et al, Metzgen et al, Enderset et al, Cheon et al, Hilddbrand et al, Rollar et al, Kin et al, Lai and Lan, Chey et al, Ryu et al, and Yakoob et al[12][13][14][15][16][17][18][19][20][21][22], who recorded 4.4-20% recurrence rate per a year.…”
supporting
confidence: 87%
“…Three previous studies investigating H. pylori resistance have been published from the Southern part of Pakistan (approximately 1400 km from the Northern region). These showed wide variations in the frequencies of antibiotic resistance to MTZ (89.0% and 48% of H. pylori isolates with resistance to MTZ not being analyzed in the third study), CLR resistance in 36.0%, 64.0%, and 33.0% of isolates, and AML resistance in 37.0%, 98.0%, and 2.0% of isolates, respectively [3638]. Geographic variations in the antibiotic resistance of H. pylori are related to the consumption of antibiotics in different communities [39].…”
Section: Discussionmentioning
confidence: 99%
“…Given that nucleotide substitutions in other antibiotic resistance-associated genes, such as rdxA associated with MTZ resistance, may not in fact be responsible for the drug resistance, clearly further experiments (mutagenic analysis by transformation) are required to substantiate any direct association of this novel nucleotide variation in the 23S rRNA gene to CLR resistance. It is also worth noting that despite the high CLR resistance rates seen in H. pylori isolates from Pakistan, a recent study has reported a low incidence of recurrence of H. pylori infection in patients [38]. …”
Section: Discussionmentioning
confidence: 99%